Antichiral edge states in an acoustic resonator lattice with staggered air flow - Yu, Letian (2021)
We present a design to achieve antichiral edge states in acoustic systems where edge states on the two parallel edges of a lattice with a strip geometry propagate in the same direction. This peculiar phenomenon is realized by using a honeycomb lattice consisting of acoustic resonators with staggered air flow; i.e., the air flow takes opposite directions in resonators belonging to different sublattices. The existence of antichiral edge states is revealed through full-wave simulations of the band structure and acoustic fields excited by a point source. Furthermore, we compare these antichiral edge states with conventional chiral edge states. It is found that the antichiral edge states are less robust than the chiral ones. Our work offers new possibilities for dispersion engineering and wave manipulations in acoustics.